O przezwyciężaniu socjalistycznej przeszłości NRD oraz "przełomu" w filmie niemieckim - Trepte, Hans-Christian (Wydawnictwo-Drukarnia Bonami/Pracownia Komparatystyki Literackiej IFP UAM, 2007)
The text is devoted to German films that deal with reckoning with the socialist past. The first films that attempted to reckon with the times of real socialism were produced after the breakthrough during the unification process of Germany. The activity of the secret Stasi police is a pivotal topic in these films. The protagonist are mostly party officers, sneaks, but also regular citizens with a conformist attitude towards the socialist reality. The films produced since the mid 1990s, usually as comedies, psychological dramas or detective stories, reveal symptoms of “nostalgia”, that is longing for stability and prosperity in East Germany.
Keywords: Ostalgia; Transformacja; Kino niemieckie po roku 1989